Clinical Characteristics of Late-Onset Cytomegalovirus Infection After Kidney Transplantation - Sirapob Nuansri (2022)
Background: Late-onset cytomegalovirus (CMV) infection (LCI) has been emerging mong solid-organ transplant recipients. We explored clinical characteristics, risk factors, and outcomes of LCI in kidney transplantation (KT) recipients. Methods: A retrospective study of all adult KT recipients with LCIs (that occurred >6 months after transplant) from 2016 to 2018 was conducted. Clinical characteristics and outcomes were extracted. Risk factors of LCI were analyzed using Cox proportional hazards models. Results: A total of 518 KT recipients were included. Ninety-eight percent had donor CMV-seropositive and recipient CMV-seropositive status (D+/R+). Ten (2%) KT recipients developed LCI with a median onset of 14 (interquartile range, 8-15) months. Those included asymptomatic CMV infection (40%) and tissue-invasive disease (60%). CMV D+/R– serostatus and a prior episode of rejection within 6 months were associated with LCI (hazard ratio, 17.35; 95% confidence interval, 3.60-83.63; P < .001) and (hazard ratio, 38.15; 95% confidence interval, 6.15-236.72; P < .001), respectively. There was no difference in the rate of allograft failure and mortality in those with LCI compared with those with early-onset CMV infection. Conclusion: LCI is uncommon after KT. Those with CMV seromismatch and a prior episode of rejection were more likely to develop LCI. Clinical and allograft outcomes were not different among each group.